Central venous-to-arterial PCO2 difference, arteriovenous oxygen content and outcome after adult cardiac surgery with cardiopulmonary bypass: A prospective observational study. Issue 4 (April 2019) - Moussa, Mouhamed D.; Durand, Arthur; Leroy, Guillaume; Vincent, Liu; Lamer, Antoine; Gantois, Guillaume; Joulin, Olivier; Ait-Ouarab, Slimane; Deblauwe, Delphine; Caroline, Brandt; Decoene, Christophe; Vincentelli, André; et al.
Abstract : BACKGROUND: Rapid identification and treatment of tissue hypoxia reaching anaerobiosis (dysoxia) may reduce organ failure and the occurrence of major postoperative complications (MPC) after cardiac surgery. The predictive ability of P CO2 -based dysoxia biomarkers, central venous-to-arterial P CO2 difference (Δ P CO2 ) and Δ P CO2 to arteriovenous oxygen content difference ratio, is poorly studied in this setting. OBJECTIVES: We evaluated the ability of P CO2 -based tissue dysoxia biomarkers, blood lactate concentration and central venous oxygen saturation measured 2 h after admission to the ICU as predictors of MPC. DESIGN: A prospective, observational cohort study. SETTING: Single-centre, academic hospital cardiovascular ICU. PATIENTS: We included adult patients undergoing cardiac surgery with cardiopulmonary bypass and measured dysoxia biomarkers at ICU admission, and after 2, 6 and 24 h. MAIN OUTCOME MEASURES: The primary endpoint was MPC, a composite of cardiac and noncardiac MPC evaluated in the 48 h following surgery. After univariate analysis of MPC covariates including dysoxia biomarkers measured at 2 h, multivariate logistic regression analyses were performed to identify the association of these biomarkers with MPC for confounders. Areas under the receiver operating characteristic curves were determined for biomarkers which remained independently associated with MPC. RESULTS: MPC occurred in 56.5% of the 308 patients analysed. Δ P CO2, blood lactate concentration and central venous oxygen saturation measured at 2 h, but not Δ P CO2 to arteriovenous oxygen content difference ratio, were significantly associated with MPC. However, only Δ P CO2 was independently associated with MPC after multivariate analysis. The areas under the receiver operating characteristic curves of Δ P CO2 measured at 2 h for MPC prediction was 0.64 (95% CI 0.57 to 0.70, P   <  0.001). CONCLUSION: After cardiac surgery with cardiopulmonary bypass, Δ P CO2 measured 2 h after ICU admission was the only dysoxia biomarker independently associated with MPC, but with limited performance. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03107572. Abstract : Supplemental Digital Content is available in the text